Regulatory Status of Genome-Edited Organisms Under the Japanese Cartagena Act - Tsuda, Mai; Watanabe, Kazuo N.; Ohsawa, Ryo (Frontiers in Bioengineering and Biotechnology, 2019)
The Japanese Government recognizes the substantial values of genome-edited agricultural organisms, and has defined in which cases these are covered by the existing regulatory framework to handle this technology. Genome editing technologies could revolutionize and accelerate plant breeding owing to the simplicity of the methods and precision of genome modifications. These technologies have spread rapidly and widely, and various genome-edited crops have been developed recently. The regulatory status of genome-edited end products is a subject of controversy worldwide. In February 2019, the Japanese Government defined genome-edited end-products derived by modifications of SDN-1 type (directed mutation without using a DNA-sequence template) as not representing “living modified organisms” according to the Japanese “Cartagena Act”. Here, we describe the classification and regulatory status of genome-edited end-products in this decision. We hope that reporting the progress in Japan toward the implementation of this regulatory approach will provide insight for scientific and regulatory communities worldwide.